The Real Exchange Rate and Growth Revisited : The Washington Consensus Strikes Back? - Berg, Andrew (IMF Working Papers; Working Paper ;, 2010)
There is good reason and much evidence to suggest that the real exchange rate matters for economic growth, but why? The "Washington Consensus" (WC) view holds that real exchange rate misalignment implies macroeconomic imbalances that are themselves bad for growth. In contrast, Rodrik (2008) argues that undervaluation relative to purchasing power parity is good for growth because it promotes the otherwise inefficiently small tradable sector. Our main result is that WC and the Rodrik views of the role of misalignment in growth are observationally equivalent for the main growth regressions he reports. There is an identification problem: Determinants of misalignment are also likely to be independent drivers of growth, and these types of growth regressions are hard-pressed to disentangle the different channels. However, we confirm that not only are overvaluations bad but undervaluations are also good for growth, a result squarely consistent with the Rodrik story but one that requires some gymnastics from the WC viewpoint.